Francopolyphonies in translation - Laëtitia Saint-Loubert (Francosphères)
Taking as its starting point Amin Maalouf’s conception of identity in Les Identités meurtrières (1998), this article will study francophonie from a translational perspective. Translation will be analysed as a linguistic transfer but also as a contact zone that brings out the alterity present in francophone texts and reveals their intrinsic plurality. Thus, translation will also be envisaged as a constitutive part of francophonie, whereby a monolingual understanding of French will give way to ‘francopolyphonies’, that is an intricate, relational space in which translation not only helps to voice polyphony, but also functions as a ‘métier à métisser’, as René Depestre puts it. While some texts will be studied as acts of self-translation, questioning the potential pitfalls of (self-)exoticism and assimilation for the francophone writer/translator, others will be analysed through a process of ‘unhoming’ French language and culture. Thus situated at the crossroads of cultural and linguistic encounters, translation will offer a transnational and translinguistic reading of francophonie, which will potentially lead to ‘franco-reciprocities’.